SINO-MYANMAR DEFENSE COOPERATION AND CHINAâ€™S EFFORTS TO BOLSTER ITS SPHERE OF INFLUENCE IN THE INDIAN OCEAN (2013-2017) - Ernasari, Cici; Banyu perwita, Anak Agung Banyu (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2018)
This paper deals with the implementation of Chinaâ€™s Defense Policy in Sino-Myanmar Defense Cooperation to bolster Chinaâ€™ sphere of influence in the Indian Ocean from 2013-2017. The rise of China has been viewed as a great phenomenon in the global political, economic and security realm, particularly in this 21st century. This rise has led China became the second biggest economy and also the strongest military in the world. This situation however pushed China to fulfill the increasing demand of energy and to seek for the alternative route. By sharing 2,204 kilometers of its border with China and having direct access to the Indian Ocean, Myanmar becomes a land bridge to get the access to Indian Ocean. Myanmar locates on tri-junction Southeast, South and East Asia and very abundance with natural resources. In the context of â€œBelt and Road Initiativeâ€ (BRI), China has implemented its defense policy through the economic and military cooperation with Myanmar. This study therefore explains the implementation of Chinaâ€™s defense policy in Sino-Myanmar defense cooperation to strengthening its position in the Indian Ocean in the search for stronger influence in the region. This research is using qualitative method qualitative research. The review of theories, literatures and previous research findings are the basic sources to form a research design and data analysis from both primary and secondary sources. This studyÂ found that China utilized its economic and defense cooperation with Myanmar to spread its hegemonic power in the region.